ANALISIS KEBANGKRUTAN BERBASIS ALTMAN Z-SCORE SEBAGAI MITIGASI KEBANGKRUTAN UMKM PARIWISATA DI SEOKOTONG LOMBOK BARAT - Pahmi, Saepul; Pratiwi, Widiya (Akuntansi research UGR, 2025)
This study aims to analyze financial ratios using the Z-score bankruptcy analysis on CV Tiga Dara, which is a tourism MSME in the Sekoktong region of West Lombok Regency. The Z-score analysis used in this study is intended to measure the financial health of the company using a sample of financial statements for the reporting period from January to December 2024. The data used in this study is secondary data taken from financial statements processed into financial ratios as used in the Altman Z-Score analysis. The results of this research show that the Z-score value obtained is 3.658, which means that financially, CV Tiga Dara is in the safe zone, indicating that the company has a healthy financial condition and does not have a significant risk of bankruptcy. Additionally, the company can also be considered to have good financial prospects and can improve its performance to achieve its business goals in the future, as the risks arising from financial management, whether from the ability to generate profits or from future debt risks, are still considered to be in a safe and healthy zone.